Who Polices the Police? - Grabiner, Gene (Social justice, 2016)
This article examines discriminatory, aggressive, and violent policing within the framework of structural and cultural violence and offers some observations about the class character of policing in America. It also provides recommendations for improved police practice, including community policing, deescalation training, more stringent public regulation of policing, and the demilitarization of police. The article concludes with a discussion of the much-debated topic of body cameras.